Hubungan faktor metabolik dan konsumsi makanan minuman manis dengan kadar gula darah pada usia 30-60 tahun di Puskesmas Simalingkar - Tarmizi, Muhammad; Siregar, Fazidah Aguslina (Talenta Publisher, 2024)
High blood glucose levels (hyperglycemia) can be caused by several conditions, including diabetes mellitus (DM). Among the top 5 nations in the world with the most DM cases in 2021 is Indonesia. There are 161,267 DM patients in North Sumatra, with 31,482 cases in Medan. Simalingkar Community Health Center is one of the health centers in Medan with the highest number of DM cases in 2022. This study intends to examine the association between blood glucose levels in individuals aged 30 to 60 at Simalingkar Community Health Center and metabolic variables, particularly obesity as assessed by body mass index (BMI) and belly circumference, as well as the consumption of sugary foods and beverages. This research is a cross-sectional study. 120 participants were included in this research sample and use accidental sampling method. Data analysis was done univariately, bivariately using the chi-square test and multivariately using logistic regression. The results showed that BMI (RP=1.701; 95% CI=1.095–2.645; p=0.022), abdominal circumference (RP=2.124; 95% CI=1.253–3.600; p=0.003) and sweet foods and beverages consumption (RP=2.042; 95% CI=1.358–3.069; p=0.001) were significantly associated with blood glucose levels. The habit of consuming sweet foods and drinks is the most dominant factor influencing a person to experience hyperglycemia (OR=3,345; 95% CI=1,512-7,387). The community is advised to control blood glucose levels by maintaining ideal body weight and reducing consumption of sweet foods and beverages to prevent type 2 DM.